Peningkatan Hasil Belajar Matematika tentang Operasi Hitung Bilangan Tiga Angka dengan Media Video Pembelajaran pada Siswa Kelas III SDN Munjul 01, Jakarta Timur - Fajar Normalita (Neolectura, 2022)
The purpose of this study was to use learning videos to helping grade III students learn more effectively about the operation of calculating three-digit numbers. For the 2022/23 academic year, the study was conducted in the first semester, in October 2022.17 grade III students from SDN Munjul 01 East Jakarta, provided data for the study. 9 male students and 8 female students. Research using the Kemmis spiral/cycle model and the Taggart MC. PTK or action research Class is a type of research with 2 cycles. Each cycle has 4 stages: a plan improvement, implementation of improvement, observation, and reflection. Data collected, both quantitative as well as qualitative. The quantitative data of each cycle are provided by formative test results. Instead observation-based qualitative data is generated by each learning cycle. Only 4 students or 25.53% who scored above KKM in the pre-cycle. 8 students (47.06%) got higher value than KKM in cycle I meeting1. On cycle I of meeting 2, precisely 52.94% of students who passed KKM. After that there is an increase in cycle II of meeting 1, with a score above KKM 12 students (70.59%). In cycle II of meetings of 2, 16 students or 94.12%, obtained a higher score than KKM. Based on these findings, can it is concluded that students' understanding of the operation of calculating three-digit numbers class III can be improved by learning improvement research with video media Learning.